SOCIALLY DISCIPLINING AND SOCIAL DRAMA IN TRADITIONAL CHILE. FLORIDA, CONCEPCIÓN , 1853-1854 - Alegría Muñoz, Paulo (Revista de Historia Social y de las Mentalidades, 2024)
The purpose of this article is to describe and  analize the persistant mechanisms involved in  conflict resolution that are likely to be found  in traditional societies in period of republican  judicial modernization. Microhistory will be  used to analize a case study from a judicial  record in the reduction of analytical scale. The  result will show us that in rural villages, the  conflict resolution mechanisms are found in  ways of socially disciplining which are enforced  by the civil and ecclesiastical authorities and  the “community” over behaviors considered  a divation from what it is expected by the  hegemonic powers before its judicialization.
Keywords: Social drama; Socially disciplining; Justice; Traditional society